Inovasi dan Strategi Pengajaran Menulis Bahasa Arab di Universitas Islam Negeri Mataram - Saputri, Risma Dewi; Husna, Nurul; Rosmala Sehan, Mahema Zulfa; Nurpahmiati, Nurpahmiati; Suparmanto, Suparmanto (Kalimatuna: Journal of Arabic Research, 2023)
This research was conducted on the basis of knowing how the process of learning Arabic as well as innovations and strategies on maharah kitabah skills. Which in learning Arabic there are four stages that must be passed first in the process of learning Arabic namely, listening skills, speaking skills, reading skills and finally writing skills (kitabah). In the process of honing writing skills, a strategy is needed in it. Because writing skills are one of the skills that are quite difficult to include in this study where we will explain how writing skills are applied at the Mataram state Islamic university, which requires all students, especially those majoring in Arabic language education, to complete their final proposal and thesis in Arabic. Therefore, in this study we will discuss how the learning strategies applied at Mataram State Islamic University are related to this skill.